Daerah Penangkapan Ikan Demersal dan Musim Perairan Bagian Selatan Pulau Gorom Kabupaten Seram Bagian Timur - Selfi Sangadji; Delly Matrutty (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2023)
The sea waters in the Southern part of Gorom Island are one of the waters that has the potential to be used as an economically important demersal fishing area. The aim of this research is to analyze and map demersal fish fishing grounds, seasons, and the distribution of fish types and sizes in the waters of the southern part of Gorom Island. Data analysis was carried out descriptively qualitatively, while specifically for fishing ground maps using Argis software. The results of the analysis show that there are three demersal fishing grounds spread across the waters of the southern part of Gorom Island, namely: "Suar Tunas", "Maduan" and "Bat". Fishing activities can take place throughout the year at these three fishing grounds, but still pay attention to weather changes which are quite extreme in the eastern season, especially July-August. Meanwhile, the peak fishing season occurs in Transition Season 1 (March-May). The types of demersal fish found in the three fishing areas are classified as economically important fish from the genus Pristipomoides sp, family Lutjanidae; Parupeneus sp. family Mullidae; Variola albimarginata family Serraenida; Scarus sp. family Scaridae; and Lethrinus sp. family Lethrinidae. These types of fish are spread unevenly across the three fishing grounds with varying fish sizes.